2013
DOI: 10.1371/journal.pone.0067081
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid and a Cytostatic Inhibitor of Glycolysis Synergistically Induce Apoptosis in Non-Small Cell Lung Cancer Cells

Abstract: Ascorbic acid (AA) exhibits significant anticancer activity at pharmacologic doses achievable by parenteral administration that have minimal effects on normal cells. Thus, AA has potential uses as a chemotherapeutic agent alone or in combination with other therapeutics that specifically target cancer-cell metabolism. We compared the effects of AA and combinations of AA with the glycolysis inhibitor 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3-PO) on the viability of three non-small cell lung cancer (NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 64 publications
2
30
0
1
Order By: Relevance
“…Several studies have investigated apoptosis as part of tumor inhibition by AsA (21,22). The present study confirmed that apoptosis in the HT1080 cells was induced and G2/M cell cycle arrest was observed following treatment with >10 mM AsA (data not shown).…”
Section: A B C Dsupporting
confidence: 85%
“…Several studies have investigated apoptosis as part of tumor inhibition by AsA (21,22). The present study confirmed that apoptosis in the HT1080 cells was induced and G2/M cell cycle arrest was observed following treatment with >10 mM AsA (data not shown).…”
Section: A B C Dsupporting
confidence: 85%
“…The difference between two groups was assessed by the Student's t test using SPSS 18.0 for Microsoft Windows. 15,19,20 ) or the combination for the indicated time. Cell death was assessed using sub-G1 analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…AA was also found to upregulate the expression of p53 to enhance cisplatin induced apoptosis in human colon cancer cells (HCT116) [12]. When AA is combined with a glycolysis inhibitor, 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen -1-one (3-PO), a synergistic induction of apoptosis via a ROSdependent pathway in non-small cell carcinoma cell lines (H1299, H661 and A549) was observed [13]. In addition, AA was shown to potentiate low dose methotrexate in inducing cancer cell death by caspase 3 and caspase 9 activation in hepatocellular carcinoma cells (Hep3B) [14].…”
Section: Ascorbic Acid Can Alter Intracellular Pathways and Cause Canmentioning
confidence: 96%